2021
DOI: 10.3390/cancers13194871
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Escalation of High-Volume Exercise during Caloric Restriction; Change in Visceral Adipose Tissue and Adipocytokines in Obese Sedentary Breast Cancer Survivors

Abstract: Aerobic exercise reduces risk for breast cancer and recurrence and promotes visceral adipose tissue (VAT) loss in obesity. However, few breast cancer survivors achieve recommended levels of moderate to vigorous physical activity (MVPA) without supervision. In a two-cohort study, feasibility of 12 weeks of partially supervised exercise was started concomitantly with caloric restriction and effects on body composition and systemic risk biomarkers were explored. In total, 22 obese postmenopausal sedentary women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 80 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…Insulin resistance was improved in both lean and obese rats, likely due in part to a reduction in visceral fat which is known to drive systemic insulin resistance. Fabian and colleagues recently reported that weight loss and visceral fat reduction improved both circulating and breast biopsy biomarkers of inflammation that have been tied to breast cancer risk [ 38 ]. Women in this clinical study all had obesity at baseline; thus, it is not clear if the same benefits would be seen in non-obese women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance was improved in both lean and obese rats, likely due in part to a reduction in visceral fat which is known to drive systemic insulin resistance. Fabian and colleagues recently reported that weight loss and visceral fat reduction improved both circulating and breast biopsy biomarkers of inflammation that have been tied to breast cancer risk [ 38 ]. Women in this clinical study all had obesity at baseline; thus, it is not clear if the same benefits would be seen in non-obese women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly established that diet-induced weight loss or weight loss through bariatric surgery both decrease breast cancer risk and improve outcomes in patients with breast cancer [ 24 , 28 34 ]. Similarly, preventing weight gain [ 35 , 36 ] and increasing physical activity [ 37 , 38 ] are also known to be beneficial. However, there is overwhelming evidence that weight loss is difficult to sustain [ 39 ], and menopause is a time when women are particularly prone to gaining weight.…”
Section: Introductionmentioning
confidence: 99%
“…Since glucose is supporting cancer progression, it has been suggested that controlled calorie intake will reduce oxidative stress and protect cells from becoming oncogenic [ 9 ]. Therefore, caloric restriction could ameliorate the risk factors in breast cancer by reducing blood glucose levels, inflammation, and the onset of angiogenesis [ 10 ].…”
mentioning
confidence: 99%
“…Calcium and vitamin D are important nutrients for bone health [ 61 ]. Numerous studies have shown the benefits of combined interventions of exercise plus diet on lipid profile, insulin, adiponectin, leptin and ghrelin [ 50 , 54 , 62 , 63 , 64 ] in breast cancer patients. Combined interventions of exercise plus diet have also found benefits in markers of inflammation, oestrogens, androgens and SHBP in other patient populations [ 65 ].…”
Section: Discussionmentioning
confidence: 99%